Kesiapan Auditor Dalam Adopsi Penggunaan Teknologi Kecerdasan Buatan Terhadap Profesi Akuntansi - Mauliza, Sri (Jurnal Riset Akuntansi dan Bisnis, 2024)
This article provides an in-depth correlational study on the level of readiness of accounting personnel and the adoption of artificial intelligence technology usage in their respective fields. The quantitative results of this study aim to examine whether the level of readiness and adoption have a positive correlation across various technologies involving the use of artificial intelligence. A descriptive research design was employed with a total of 50 accounting personnel selected through purposive sampling from chosen public and private universities as well as local government units in Cavite. The collected data were analyzed using frequency counts, percentages, weighted mean, standard deviation, and Spearman's Rho method, while maintaining strict confidentiality. The findings revealed that participants were moderately ready to use AI software applications, slightly ready to use Cloud technology, and fairly ready to use Blockchain technology. It was also disclosed that participants were moderately adaptive to using AI software applications, slightly adaptive to using Cloud technology, and moderately adaptive to using Blockchain technology in their accounting profession. Furthermore, it was revealed that there is a positive correlation between the level of readiness and adoption in the use of all AI technologies.